Knocking down of lncRNA SBF2-AS1 inhibits proliferation, invasion and induces apoptosis of colorectal cancer through regulating PTEN: Silence of lncRNA SBF2-AS1 inhibits the progression of CRC - Cai, Yanyang; Yan, Haibin; Wang, Fang; Xie, Lufan (Cellular and Molecular Biology, 2023)
To illustrate the potential function of lncRNA SBF2-AS1 in the progression of colorectal cancer (CRC) and the molecular mechanism. The relative level of SBF2-AS1 in CRC tissues and cell lines was determined by qRT-PCR. Its level in CRC patients with different tumor stages and tumor sizes was examined. After the knockdown of SBF2-AS1, proliferative, invasive abilities and apoptotic rate of CRC cells were evaluated. The correlation between SBF2-AS1 and PTEN was analyzed in CRC tissues. Furthermore, the subcellular distribution of SBF2-AS1 was assessed. Through RIP and ChIP assay, the interaction between SBF2-AS1 and PTEN was identified. Finally, the involvement of PTEN in SBF2-AS1-mediated CRC progression was analyzed. SBF2-AS1 was upregulated in CRC tissues and cell lines. Its level remained higher in CRC with worse tumor stage and larger tumor size. Knockdown of SBF2-AS1 attenuated proliferative, invasive abilities, but induced apoptotic rate of SW480 and DLD1 cells. A negative correlation was identified between expression levels of SBF2-AS1 and PTEN in CRC tissues. PTEN level was negatively regulated by SBF2-AS1. Subcellular distribution analysis indicated that SBF2-AS1 was mainly expressed in the nucleus. Furthermore, the RIP assay proved the binding of SBF2-AS1 to EZH2 and SUZ12. Knockdown of SBF2-AS1 attenuated the recruitment ability of EZH2 to PTEN. Notably, inhibited proliferation by transfection of sh-SBF2-AS1 1# was partially reversed after co-transfection of sh-PTEN. LncRNA SBF2-AS1 is upregulated in CRC. Knocking down of lncRNA SBF2-AS1 inhibits proliferation, and invasion and induces apoptosis of colorectal cancer by interacting with EZH2 to downregulate PTEN level.